Surge in diabetic ketoacidosis in children with Type 1 diabetes during COVID-19 pandemic – A report from a tertiary care center in Pune, India - Guruprasad Hassan Shankar; Varsha Sharma; Bhakti Sarangi; Ajay Walimbe; K C Prithvichandra Markal; Venkat Sandeep Reddy (Journal of Pediatric Critical Care, 2021)
As the COVID-19 pandemic evolves, an increasing number of concurrent associations are being reported including several postinfectious phenomena. The role of diabetes mellitus (DM) and its implications in increased severity and mortality of adults with COVID-19 is established. COVID-19 is known to cause hyperglycemia and worsen glycemic control in adults with active infection. However, the association in pediatric population is not well established. The interplay between biological, psychosocial, and economic factors for increased association of COVID-19 with Type 1 DM and/or presentation with diabetic ketoacidosis (DKA) is not clear. We briefly describe a surge in the number of children with DKA as experienced in our center in the course of the ongoing pandemic with a brief evaluation of all the abovementioned factors.